2014
DOI: 10.1631/jzus.b1400003
|View full text |Cite
|
Sign up to set email alerts
|

Diversity change of microbial communities responding to zinc and arsenic pollution in a river of northeastern China

Abstract: Pollution discharge disturbs the natural functions of water systems. The environmental microbial community composition and diversity are sensitive key indicators to the impact of water pollutant on the microbial ecology system over time. It is meaningful to develop a way to identify the microbial diversity related to heavy metal effects in evaluating river pollution. Water and sediment samples were collected from eight sections along the Tiaozi River where wastewater and sewage were discharged from Siping City… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 31 publications
3
11
0
Order By: Relevance
“…The occurrence and distribution of Acinetobacter spp. in freshwater resources in the study further validated the findings in other reports [29,31].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The occurrence and distribution of Acinetobacter spp. in freshwater resources in the study further validated the findings in other reports [29,31].…”
Section: Discussionsupporting
confidence: 91%
“…The study reported that the relative abundance of Acinetobacter species was 0.5% of the total bacterial community. In 2014, Zhao and others [31] isolated a set of bacteria from the zinc and arsenic polluted river in Northeastern China, where bacteria belonging to the genus Acinetobacter were found to be prominent. The occurrence and distribution of Acinetobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…Sewage water is heavily loaded with chemical and biological contaminants, excess of organic compounds, heavy metals, pesticides, traces of oil and grease, as well as pharmaceuticals like antimicrobial agents (Heberer, ; Joss et al., ). This creates a harsh and selective environment (e.g., eutrophic, anaerobic and chaotropic conditions), which is likely to select specialized and well‐adapted microorganisms (Korlević et al., ; Zhao et al., ). Indeed, a robust phylogenetic trend based on lower cDNA prevalence in the inlet compartments was found, suggesting conservation of transcriptional activity in large taxonomic groups (e.g., phylum and class).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that pollution of environmental sites either with fuel oil or metals can affect the microbial diversity and only few types of bacteria such as Acinetobacter spp. were able to resist and dominate such polluted areas (Bordenave et al, 2007 ; Zhao et al, 2014 ). Moreover, these bacteria are able to degrade various pollutants and organic compounds and have an important role in environmental bioremediation (Adegoke et al, 2012 ; Cray et al, 2013 ).…”
Section: Global Remarksmentioning
confidence: 99%